G455(P) Lower respiratory tract infection in patients with neurological impairment: a narrative review on microbiota and antimicrobial interventions. (12th March 2018) - Burgess-Shannon, J; Thomson, L
Abstract : Background: Lower respiratory tract infections (LRTI) are a major cause of morbidity and mortality in patients with neurological impairment. Prophylactic antibiotics and eradication of colonisers are approaches employed in the prevention of recurrent LRTI. Aims: To determine the evidence base for this practice in children with neurological impairment. Methods: An electronic database search identified studies reporting on outcomes of efficacy for antimicrobial interventions and microbial findings relevant to LRTI in our population of interest. Results were synthesised into a narrative review. Results: Our search revealed a small case-series suggesting nebulized tobramycin may be effective in reducing the frequency of pneumonias and associated hospitalisations. We identified 5 papers focusing on microbial findings – there was significant variability in the frequency of bacterial isolation, and in the species identified. These studies were heterogeneous and subject to individual biases which limits the wider applicability of results. Conclusions: The direct evidence for antimicrobial interventions as a prophylactic strategy against LRTI in patients with neurological impairment is lacking and warrants further research. In addition, we still lack a clear understanding of the microbiota contributing to respiratory pathology, which could inform therapeutic targets.